In vivo and in vitro study of co-expression of LMP1 and Cripto-1 in nasopharyngeal carcinoma - Ye,Qing (2020)
Abstract Introduction: Nasopharyngeal carcinoma, an epithelial-derived malignant tumor which because of its anatomical location and atypical early symptoms, when diagnosed invasion and metastasis often have occurred. This requires a better understanding of the development mechanism, identifying diagnostic markers, and developing new treatment strategies. Objective: To study the relationship of LMP1 and Cripto-1 in nasopharyngeal carcinoma. Methods: The expression of LMP1 and Cripto-1 in specimens obtained from nasopharyngeal carcinoma patients (n = 42) and nasopharyngitis patients (n = 22) were examined. The expression of LMP1 and Cripto-1 in LMP1-negative and LMP1-positive (CNE1-LMP1) cells were also examined. Results: The expression of LMP1 and Cripto-1 was significantly higher in nasopharyngeal carcinoma than in nasopharyngitis (p < 0.05). Their expression in nasopharyngeal carcinoma with metastasis were significantly higher than that without metastasis (p < 0.05), which was correlated with TNM staging (p < 0.05). High Cripto-1 expression and high proliferation rate were seen in CNE1-LMP1 cells. Conclusions: The expression of LMP1 and Cripto-1 in nasopharyngeal carcinoma is positively related. Their co-expression might contribute to the proliferation and metastasis of nasopharyngeal carcinoma.